Inflammaging phenotype in rhesus macaques is associated with a decline in epithelial barrier-protective functions and increased pro-inflammatory function in CD161-expressing cells - Walker, Edith M. (GeroScience, 2019)
The development of chronic inflammation, called inflammaging, contributes to the pathogenesis of age-related diseases. Although it is known that both B and T lymphocyte compartments of the adaptive immune system deteriorate with advancing age, the impact of aging on immune functions of Th17-type CD161-expressing innate immune cells and their role in inflammaging remain incompletely understood. Here, utilizing the nonhuman primate model of rhesus macaques, we report that a dysregulated Th17-type effector function of CD161(+) immune cells is associated with leaky gut and inflammatory phenotype of aging. Higher plasma levels of inflammatory cytokines IL-6, TNF-α, IL-1β, GM-CSF, IL-12, and Eotaxin correlated with elevated markers of gut permeability including LPS-binding protein (LBP), intestinal fatty acid binding protein (I-FABP), and sCD14 in aging macaques. Further, older macaques displayed significantly lower frequencies of circulating Th17-type immune cells comprised of CD161(+) T cell subsets, NK cells, and innate lymphoid cells. Corresponding with the increased markers of gut permeability, production of the type-17 cytokines IL-17 and IL-22 was impaired in CD161(+) T cell subsets and NK cells, along with a skewing towards IFN-γ cytokine production. These findings suggest that reduced frequencies of CD161(+) immune cells along with a specific loss in Th17-type effector functions contribute to impaired gut barrier integrity and systemic inflammation in aging macaques. Modulating type-17 immune cell functions via cytokine therapy or dietary interventions towards reducing chronic inflammation in inflammaging individuals may have the potential to prevent or delay age-related chronic diseases and improve immune responses in the elderly population. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11357-019-00099-7) contains supplementary material, which is available to authorized users.